Evropske smernice za učenje tujih jezikov na predšolski in razredni stopnji osnovne šole - Karmen Pižorn; Mihaela Brumen (Journal of Elementary Education, 2008)
European Guidelines for Teaching Foreign Languages in Preschool and Elementary School. The article presents some common European references that are used for language learning and teaching. Common European language policy demands that multilingual individuals be self-confident in preserving their identity that makes them different in a multilingual world. Teaching foreign languages at the primary level is a necessity for contemporary society, not only in Europe but also worldwide. It is a fact that has been scientifically proven through practice. Globalisation, mobility and the common market require multilingual speakers. The article introduces some of the essential issues of the Action Plan 2004-2006, which supports multilingual competency in Europe and suggests adding two additional foreign languages to the primary level curriculum. Some main issues of The Common European Framework of Reference, which is increasingly used in making reforms to the national curricula, are also presented. The European Index of Language  competences is also provided in the article. It includes some of the main issues concerning additional foreign language stimulation at the primary level. The conclusion deals with some issues of the Slovenian foreign language policy.